Geometrical isomerism directed electrochemical sensing - Kottaichamy, Alagar Raja; Begum, Shabbah; Devendrachari, Mruthyunjayachar Chattanahalli; Bhat, Zahid Manzoor; Thimmappa, Ravikumar; Kotresh, Harish Makri Nimbegondi; Vinod, Chathakudath Prabhakaran; Thotiyl, Musthafa Ottakam (Analytical Chemistry, 2020)
We report the independent role of isomerism of secondary sphere substituents over their nature, a factor often overlooked in molecular electrocatalysis pertaining to electrochemical sensing, by establishing that isomerism redefines the electronic structure at the catalytic reaction center via geometrical factors. UV-vis spectroscopy and X-ray photoelectron spectroscopy suggest that a substituent's isomerism in molecular catalysts conjoins molecular planarity and catalytic activation through competing field effects and resonance effects. As a classical example, we demonstrate the influence of isomerism of the -NO2 substituents for the electrocatalytic multi electron oxidation of As(III), a potentially important electrochemical pathway for water remediation and arsenic detection. The isomerism dependent oxidative activation of catalytic center leads to a nonprecious molecular catalyst capable for direct As(III) oxidation with an experimental detection limit close to WHO guidelines. This work opens up an unusual approach in analytical chemistry for developing various sensing platforms for challenging chemical and electrochemical reactions.